Auditor Performance Within Moderasi Compliance and the Influence of Audit Structure, Good Governance, and Organizational Culture - John Villinds Timbang Weigh; Rina Anindita (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The purpose of this study is to investigate the role of audit structure, Good Governance, and organizational culture in influencing the performance of auditors on the Audit Board of the Republic of Indonesia (BPK RI). This quantitative research employs a survey conducted on auditors of government agencies in six regions of Indonesia, and the survey tool employs questionnaires, which are delivered to 320 persons and returned by all of them. Partial Lease Square Analysis Using the Structural Equation Model (SEM) (PLS). According to the findings, the Audit Structure, excellent governance, and corporate culture all have a favorable impact on auditor performance. Compliance moderation in the relationship Audit structure, good governance does not strengthen or weaken the relationship Audit structure, good governance to auditor performance in the variable of compliance moderation. Meanwhile, compliance moderation appears to be capable of strengthening the link between organizational culture and auditor performance. The study's findings are valuable for auditors and researchers in understanding the elements that affect auditor performance as well as the effect of compliance moderation on auditor performance within the Auditor of the Audit Board of the Republic of Indonesia (BPK RI).